Undernotification of anaphylaxis deaths in Brazil due to difficult coding under the ICD‐10 - Luciana Kase Tanno; Fernando Ganem; Pascal Demoly; Cristiana M. Toscano; Ana Luiza Bierrenbach (2012)
Abstract Background Undernotification is well recognized as a key challenge to the study of anaphylaxis mortality, but it is seldom mentioned that one of its reasons is the difficult coding of the condition under the tenth revision of the international classification of diseases ( ICD ‐10), given that there are no anaphylaxis‐specific ICD ‐10, which are considered valid for coding underlying causes‐of‐death, and that official mortality statistics consider exclusively the underlying and disregard the contributing causes‐of‐death data recorded on death certificates. Brazilian mortality data were used as a case study to call attention to the inadequacy of the ICD ‐10 for the measurement of anaphylaxis deaths. Methods Underlying and contributing causes‐of‐death data were used to estimate the rates of anaphylaxis deaths in the country over the years 2008–2010. Results Of 498 anaphylaxis deaths were found, of which 75% were classified as ‘definite’ and 25% as ‘possible anaphylaxis deaths’. The average national rate for these years was 0.87 per million per year. None of these deaths would have been found had we exclusively considered information from the underlying cause‐of‐death field. Conclusion/Recommendations The study of anaphylaxis mortality using secondary data requires the use of information derived from the underlying as well as from the contributing causes‐of‐death fields. Coding definitions should be standardized with a view of enabling trend analyses and international comparisons. The ICD ‐11 revision is a unique opportunity to improve the coding system so as to facilitate epidemiological studies of anaphylaxis mortality. Educational interventions targeted at improving the quality of death certificate completion are urgently needed.